2021
DOI: 10.1177/1759720x211002682
|View full text |Cite
|
Sign up to set email alerts
|

Cycling of tumor necrosis factor inhibitors versus switching to different mechanism of action therapy in rheumatoid arthritis patients with inadequate response to tumor necrosis factor inhibitors: a Bayesian network meta-analysis

Abstract: Introduction: For patients with rheumatoid arthritis (RA) with an inadequate response to tumor necrosis factor inhibitors (TNFi), main options include cycling onto a different TNFi or switching to a biologic/targeted synthetic disease-modifying antirheumatic drug with a different mechanism of action (MOA). This network meta-analysis (NMA) assessed comparative clinical efficacy of cycling versus switching. Methods: We conducted a literature search in MEDLINE, Embase, and Cochrane Library. Outcomes included prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 64 publications
0
10
1
1
Order By: Relevance
“…This treatment approach is supported by the recent European Alliance of Associations for Rheumatology guidelines, which propose that if a ts/bDMARD has failed, treatment with another ts/bDMARD should be considered, whereas if a TNFi therapy has failed, patients may receive an agent with another mechanism of action or a second TNFi [ 2 ]. However, a network meta-analysis comparing cycling (i.e., using another agent with the same mode of action) versus switching (i.e., using agents with different modes of action) among RA treatments found that the latter approach was associated with improved clinical outcomes and lower withdrawal rates [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This treatment approach is supported by the recent European Alliance of Associations for Rheumatology guidelines, which propose that if a ts/bDMARD has failed, treatment with another ts/bDMARD should be considered, whereas if a TNFi therapy has failed, patients may receive an agent with another mechanism of action or a second TNFi [ 2 ]. However, a network meta-analysis comparing cycling (i.e., using another agent with the same mode of action) versus switching (i.e., using agents with different modes of action) among RA treatments found that the latter approach was associated with improved clinical outcomes and lower withdrawal rates [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current analysis had some important differences compared with other studies, which had suggested better outcomes when patients were switched to a different class of biologics after a TNFi failure rather than rechallenged with another TNFi (i.e., cycling) [33][34][35][36]. In our study, CDAI was the primary outcome, whereas in some similar analyses, persistence was used as an outcome [33,34,36]; there were only 6 months of follow-up; and approximately one-third of the TNFi initiators and more than half of the IL-6Ri initiators were on their second treatment switch.…”
Section: Discussionmentioning
confidence: 84%
“…There was a high proportion of patients who had prior TNFi exposure (88.8%-92.1%) in our study. Literature suggests that a better treatment response would occur when switching from a TNFi to an alternative mechanism of action therapy [33][34][35][36]. Since many patients initiating a TNFi had already failed another TNFi in our b/ts-experienced cohort, we investigated for a potential selection bias in patients who received a follow-on TNFi.…”
Section: Discussionmentioning
confidence: 99%
“…Серонегативность по АЦЦП коррелировала с повышением риска развития инфекций на фоне лечения ТЦЗ [176]. Клинически и экономически более оправданным вариантом коррекции терапии при неэффективности иФНО-α является переход к ГИБП с альтернативным механизмом действия [177][178][179][180][181][182]. При сравнении РТМ и ТЦЗ их эффективность после потери эффекта иФНО-α была сопоставима [183].…”
Section: особенности терапии аццп-негативного раunclassified